2018
DOI: 10.1016/j.jsps.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication with antibiotics in Saudi Arabia

Abstract: The relative high prevalence of self-medication with antibiotics necessitates taking serious steps by health authorities to implement the law of forbidding the sale of antibiotics without prescription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 22 publications
10
63
2
1
Order By: Relevance
“…This includes tackling the use of AMs without a prescription, which is considered a form of AM 'misuse' that can potentially accelerate the emergence of resistant microorganisms (WHO, 2015b). Over the last decades, numerous studies on self-medication with antibiotics, conducted in different parts of the world, have sought to determine the prevalence, risks and/or factors related to 'inappropriate' antibiotic use (e.g., Borg and Scicluna, 2002;Grigoryan et al, 2007;Elmasry et al, 2013;Albawani et al, 2017;Alghadeer et al, 2018). Although tracking OTC sales is challenging in most countries (WHO, 2015b), according to a review of Alhomoud et al (2017, p. 4), "it has been estimated that more than 50% of antibiotics are purchased without a prescription and used over-the-counter in most parts of the world".…”
mentioning
confidence: 99%
“…This includes tackling the use of AMs without a prescription, which is considered a form of AM 'misuse' that can potentially accelerate the emergence of resistant microorganisms (WHO, 2015b). Over the last decades, numerous studies on self-medication with antibiotics, conducted in different parts of the world, have sought to determine the prevalence, risks and/or factors related to 'inappropriate' antibiotic use (e.g., Borg and Scicluna, 2002;Grigoryan et al, 2007;Elmasry et al, 2013;Albawani et al, 2017;Alghadeer et al, 2018). Although tracking OTC sales is challenging in most countries (WHO, 2015b), according to a review of Alhomoud et al (2017, p. 4), "it has been estimated that more than 50% of antibiotics are purchased without a prescription and used over-the-counter in most parts of the world".…”
mentioning
confidence: 99%
“…Other ways included: shifting antibiotics, sharing antibiotics, and keeping leftovers (27-29, 35, 39, 40, 43, 44, 48, 50-52, 56, 59, 61, 65, 67, 77, 78, 80 . Besides, healthcare professionals should be educated regarding rational usage of antibiotics, and also medical curriculum should be revised to address this problem (25,28,33,34,37,38,40,46,52,64,69,79,82). Other recommendations followed by accessible healthcare for all (26,77) and more research and periodic survey (32,55,74) for exploring the public awareness, determining the level of microbial resistance, and assessing the effectiveness of different approaches of interventions.…”
Section: Common Illnesses Rendering Smamentioning
confidence: 99%
“…These findings are in agreement with available published literature which indicated that intentions for selfmedication with antibiotics result from the need to save money and the desire to act promptly to treat suspected or confirmed bacterial infections (Carvajal-Vélez et al, 2016;Chalovich and Eisenberg, 2013;Le et al, 2011). This knowledge of the condition is obtained from the health facility after the initial visit and knowledge of the exact medication that was provided (Viberg et al, 2010;Alghadeer et al, 2018).…”
Section: Determinants Of Antimicrobial Use In Diarrhoea Managementmentioning
confidence: 99%
“…Diarrhoeal disease can be prevented by simple measures like personal hygiene and environmental sanitation; nonetheless, antibiotic therapy remains one of the common measures used to curb the disease despite the presence of less invasive solutions such as the Oral Rehydration Salts which are key remedies in treating childhood diarrhoea (Padhy et al, 2017;Mahapatra et al, 2015;Gwimile et al, 2012). This key role of antibiotics has contributed to high usage of antibiotics in management of diarrhoea which is contributing to increased cases of antimicrobial resistance (Padhy et al, 2017;Alghadeer et al, 2018). Oral Rehydration Salts (ORS) and Zinc supplementation during diarrhoea illness has been shown to reduce the duration and severity of diarrhoea episodes in many countries which in the long run reduces morbidity and mortality among under-five children (Carvajal-Vélez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%